Morphological, optical and thermal characterisation of aerogel-epoxy composites for enhanced thermal insulation - Krishnaswamy, Suryanarayanan; Bhattacharyya, Debabrata; Abhyankar, Hrushikesh; Marchante Rodriguez, Veronica; Huang, Zhaorong; Brighton, James (SAGE, 2018)
The present work explores the possibility of introducing aerogel at different stages of the epoxy resin cure to identify the most effective method that ensures minimal destruction of the aerogel particles. The aerogel particles are added at 0.5 h, 1 h and 1.5 h after the resin and the hardener are mixed together. Additionally, the effect of a wetting agent that improves the interface between the aerogel and the resin is also investigated. The different materials are characterised using optical images and ESEM-EDX to determine the most effective processing route. Additional data are also provided by determining the different material’s optical transmittance and reflective characteristics. From the experimental results, it is observed that the addition of aerogel at the 1-h mark proves to be the most efficient route to follow. In addition, the wetting agent displays a negligible effect on the samples in the study; hence, its usage is advocated due to its influence on the interface strength. Therefore, the aerogel/epoxy/wetting agent sample with the aerogel added at the 1 h mark looks promising. A 13.3% decrease in thermal conductivity when compared with the pure resin/hardener sample along with the damage coefficient value of 0.183 demonstrates the material’s potential for thermal insulation applications.
Keywords: Aerogel; epoxy; thermal insulation; damage coefficient; composite materials